Desain Rancang Bangun Sistem Informasi Pendaftaran Peserta Didik Berbasis Hybird - Dinni, Ririn Nur; Sifaunajah, Agus (SAINTEKBU, 2022)
In supporting good, synchronous, and fast communication, the school facilitates one of them by building a New Student Registration Information System Based on the Android Operating System. The purpose of this study is to determine the number of dormitory quotas at YPPBU and to design a mobile-based YPPBU capacity information system. The research uses qualitative methods and testing is carried out in system development using the Black Box method. This Black Box testing method is used to determine whether a software is functioning properly and correctly. The results of this study use the New Student Registration application to simplify and speed up the registration system, as well as registration that can be done without having to come to school and make it easier for schools to monitor students who register. The application used has a good suitability of functions and runs correctly.